MANAGEMENT STRATEGIES FOR NECK CONTRACTURES FOLLOWING BURNS: A COMPREHENSIVE REVIEW - Mohamed A. Ellabban, Samia Saied, Ahmed A. A. Ali, Ibrahim S. A. Rihan (Chelonian Research Foundation, 2024)
Burns to the head and neck can lead to several serious complications, including difficulties with swallowing and speaking, swelling in the airways, and severe problems with taste, hearing, smell, and vision. Reconstruction of the face and neck is among plastic surgery's most complex and critical procedures. This region demands a large volume of soft tissue for functional restoration and requires high-quality tissue to achieve optimal cosmetic outcomes. Post-burn contractures in the neck are particularly challenging, as they can severely limit motion, disrupt facial harmony, and lead to profound aesthetic and functional deficits. The neck is the critical connector between the head and body, and mobility is essential for daily functions like breathing, swallowing, and visual orientation. Burn-induced flexion contractures in this region can cause severe functional limitations (e.g., restricted head movement) and aesthetic deformities, significantly impacting the patient's quality of life.